Middle Eastern Everyday Life in S.S. Kondurushkin’s Magazine Essays at Beginning of Twentieth Century - S. A. Dubrovskaya; V. P. Kirzhaeva; S. M. Vladimirova (Научный диалог, 2021)
The problem of the presentation of the Middle Eastern everyday life in the early prose of S.S. Kondurushkin (1874—1919), an active participant in the literary and social life of Russia at the turn of the XIX—XX centuries is examined in the article. On the basis of the essay cycle “From Wanderings in Syria” and other works of the early 1900s, an analysis of the methods of recreating the Middle Eastern everyday life is presented. The narrative strategies that underlie the Middle Eastern narrative of the Russian traveler are studied. This makes it possible to clarify the characteristics of the genre of the travel sketch in the general context of Russian literature at the turn of the century, which determines the scientific novelty and relevance of the article. The authors examine in detail the essays “Greeks in Palestine and Syria”, “Terra incognita”, “La Bayadere”, “Akulina in Tripoli”. The consistent change of the exposing discourse of political journal-ism to various forms of “ethnographic” narrative are substantiated in the article. The tasks set required the use of traditional methods of academic literary criticism, as well as techniques of cultural linguistics, imagology, imperial and colonial studies. A number of archival materials are introduced into scientific circulation, in particular, letters from N.K. Mikhailovsky addressed to S.S.Kondurushkin.